Gender Blind Policy pada Praktik Pelecehan Seksual Online dan Nonconsensual Initimate Image di Indonesia - Deshyara Frizma Aulia; Laras Destriana; Ika Arinia Indriyany (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
Online sexual harassment and the distribution of nonconsensual intimate images (NCII) are forms of gender-based violence in the digital space, the prevalence of which continues to increase in line with the rapid growth of internet penetration in Indonesia. Although women are statistically the most vulnerable and affected group, existing legal policies in Indonesia tend to be gender-blind that is, they do not recognize and integrate gender perspectives in the formulation of norms and mechanisms for handling them. This study aims to analyze how the gender-blind character of existing regulations, including the Electronic Information and Transactions Law (UU ITE) and related legal instruments, contributes to inadequate protection for victims of online sexual harassment and NCII. Using a juridical-normative approach and a feminist legal perspective, this study examines the gap between gender-neutral policy formulations and the reality of structural inequality experienced by victims. The results show that a gender-blind approach obscures the power dimension in gender-based cybercrime, hinders access to justice for victims, and weakens the effectiveness of perpetrator punishment. This study recommends gender-responsive policy reform as a fundamental step in providing substantive and equal legal protection for victims in Indonesia.